Physical and Thermal Properties of MgCl2 mixed with NaCl at Various Ratios for Solar Thermal Energy Storage Application - Gunawati, Gunawati; Setiawan, Adi; Syahputri, Riana; Riskina, Shafira (Politeknik Negeri Lhokseumawe, 2025)
Latent heat storage is a system capable of absorbing and releasing heat energy when a material undergoes a phase change. The material often used in this system is referred to as PCM (Phase Change Material). One of commonly used material for heat storage is salt. This type of material was chosen due to its low-cost and better in chemical-physical properties. This study aimed to find out the effect of combining NaCl with MgCl2 on the properties and performance of PCM. For preparation, MgCl2 was added to NaCl followed by manual mixing and grinding to ensure homogeneity. The samples were placed inside the muffle furnace and heated to 600°C. Next, the samples were evaluated for physical properties such as density, specific heat, and thermal conductivity, and tested for charging and discharging performance using a thermal box. The test results suggested that the higher MgCl2 content, the more specific heat capacity and thermal conductivity. However, it is inversely proportional to the density, where the lower the MgCl2 portion, the higher the density value. This caused the rate of thermal energy absorption and energy storage capacity increased significantly